Curcumin Targets in Inflammation and Cancer - Deguchi, Atsuko (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2015)
Curcumin (1,7-bis(4-hydroxy-3-methoxyphenyl)-1,6-heptadiene-3,5-dione) is commonly used as a spice, food additive or dietary pigment. Accumulating evidence suggests that curcumin has several pharmacologic effects, including anti-inflammatory, anti-oxidant and anti-cancer activities. The molecular mechanisms underlying the targets of curcumin are diverse and involve combinations of multiple signaling pathways, including NF-ΚB and STAT3 signaling. Thus, curcumin is one of the most promising phytochemicals that target various cancers and inflammation-mediated diseases. Clinical trials have been ongoing or completed for various cancers, including breast, pancreatic and colorectal cancers, and multiple myeloma. In this review, the molecular mechanisms and the issue of bioavailability are mainly discussed.
Keywords: cancer